2021
DOI: 10.1186/s12885-021-08409-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between multimorbidity and depression among breast cancer survivors within the UK Biobank cohort: a cross-sectional study

Abstract: Background Advances in the early detection of cancer and its treatment have resulted in an increasing number of people living with and beyond breast cancer. Multimorbidity is also becoming more common in this population as more people live longer with breast cancer and experience late effects of cancer treatment. Breast cancer survivors have heightened risk of depression, but to what extent multimorbidity affects the mental health of this population is less clear. This study aims to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…Moreover, psychological distress (symptoms of depression and anxiety) has been associated with poorer physical function and high mortality risk (17). Approximately 38% of the breast cancer patients in the study were diagnosed with depression and 32% of them with anxiety based on PHQ2 (18) and GAD2 (19) questionnaires.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, psychological distress (symptoms of depression and anxiety) has been associated with poorer physical function and high mortality risk (17). Approximately 38% of the breast cancer patients in the study were diagnosed with depression and 32% of them with anxiety based on PHQ2 (18) and GAD2 (19) questionnaires.…”
Section: Discussionmentioning
confidence: 98%
“…Participants who had ever seen a psychiatrist for nerves, anxiety, tension, or depression were thought to fulfill this criterion. Thirdly, we widened the definition of depression phenotypes by including the measurement of two-item Patient Health Questionnaire (PHQ-2) ( 18 ). At recruitment, participants were asked the frequency of depressed mood and unenthusiasm/disinterest in last 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“… 21 , 22 Many studies have reported that comorbidity and multimorbidity at the time of cancer diagnosis, and measured by the Charlson Comorbidity Index (CCI), 10 , 23 , 24 or simple count of some strictly selected comorbid conditions and their relationships with psychological distress among breast cancer patients. 4 , 8 , 10 , 17 , 23 , 25 - 29 However, the influence of individual comorbid conditions on mental health may vary, the CCI includes only 19 chronic physical conditions (without psychiatric conditions) and it has been validated to predict mortality, but maybe not associated with poor mental health. 10 Few studies to date have investigated multimorbidity including broad chronic conditions and their associations with breast cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Few studies to date have investigated multimorbidity including broad chronic conditions and their associations with breast cancer outcomes. 8 , 10 , 23 , 26 - 30 Some studies have been limited to older populations (ie, ages ≥60, ≥65, or ≥70 years), 10 , 15 , 31 cancer registry-based studies, 4 , 17 , 23 or survey studies without detail data on comprehensive comorbidities. 11 , 25 , 26 , 29 , 31 Very limited data are available on the associations of the presence of multimorbidity with mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation